The design of information systems the village office of Silaberanti - Abi ardiyanto Saiful; Karnadi (International Journal Cister, 2022)
On when searching for a letter that has been made before. The process of collecting data on incoming and outgoing letters from the village office is also still manual. So prone to errors and data loss. The Silaberanti Village Office requires a more secure and faster mail processing. Based on the existing background, the Silaberanti Wanting Village Office can handle these problems, such as processing letters so as to produce appropriate mail processing reports. So that it can accelerate the performance of the Village Office employees Silaberanti records incoming and outgoing letters